2011
DOI: 10.1152/ajpheart.00519.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reduced NO signaling during pregnancy attenuates outward uterine artery remodeling by altering MMP expression and collagen and elastin deposition

Abstract: Hale SA, Weger L, Mandala M, Osol G. Reduced NO signaling during pregnancy attenuates outward uterine artery remodeling by altering MMP expression and collagen and elastin deposition. Am J Physiol Heart Circ Physiol 301: H1266 -H1275, 2011. First published August 19, 2011 doi:10.1152/ajpheart.00519.2011.-Recent findings indicate that endothelial nitric oxide (NO) plays a key role in uterine artery outward circumferential remodeling during pregnancy. Although the underlying mechanisms are not known, they likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 72 publications
(97 reference statements)
1
24
0
Order By: Relevance
“…2 NO is a free radical and is also an important cellular signalling molecule in many physiological and pathological processes and it is 45 showed that NO-mediated redox regulation is the mechanism of PTEN protein degradation (phosphatase and tensin homologue), which accounts for PTEN loss in neurodegeneration such as in Alzheimer's disease, in which NO plays a critical pathophysiological role. Hale et al 46 reported that NO signalling is also involved in uterine vascular remodelling during pregnancy, thus altering the matrix metalloproteinase expression as well as collagen and elastin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…2 NO is a free radical and is also an important cellular signalling molecule in many physiological and pathological processes and it is 45 showed that NO-mediated redox regulation is the mechanism of PTEN protein degradation (phosphatase and tensin homologue), which accounts for PTEN loss in neurodegeneration such as in Alzheimer's disease, in which NO plays a critical pathophysiological role. Hale et al 46 reported that NO signalling is also involved in uterine vascular remodelling during pregnancy, thus altering the matrix metalloproteinase expression as well as collagen and elastin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…the reduced uterine perfusion pressure model [28], hypertension, e.g. systemic nitric oxide synthase (NOS) inhibition [29,30] and proteinuria, e.g. the angiotensinogen/renin overexpression transgenic rat model [31]; these, however, likely do not recapitulate its true etiology [32,33].…”
Section: Preeclampsia the ‘Disease Of Theories'mentioning
confidence: 99%
“…Placental ischemia is thought to lead to widespread activation/dysfunction of the maternal vascular endothelium. This enhances the formation of vasoactive factors like endothelin (ET-1) (13) and thromboxane A2 (TXA 2 ) (22), as well as it increases vascular sensitivity to angiotensin II, and decreases the formation of vasodilators such as nitrous oxide (17) and prostacyclin (PGI 2 ) (13). Maternal endothelial cell activation/dysfunction enhances the synthesis of inflammatory cytokines such as tumor necrosis factor alpha (TNF-α).…”
mentioning
confidence: 99%